Peran Pemetaan Digital (Go Maps) Dalam Pengembangan Ekonomi Lokal: Studi Kasus Umkm Desa Susuk - Riskha Setianingsih; Umi Nur Habibah; Siti Ardianti; Nurbaiti Nurbaiti (Jurnal Manajemen, Bisnis dan Kewirausahaan, 2026)
This study discusses the role of digital mapping through Google Maps (Go Maps) in supporting local economic development, using a case study of MSMEs in Susuk Village, Tiganderket District, Karo Regency. The method employed is Participatory Action Research (PAR), an approach that actively involves the community and MSME actors throughout the research process—from location identification, data collection, and documentation to the digitalization of business points using the Google Maps platform. This collaborative method not only ensures accurate data representation but also strengthens the sense of ownership among participants. The findings indicate that digital mapping significantly contributes to enhancing the visibility, accessibility, and overall image of local MSME businesses. With business locations accurately listed on Google Maps, consumers can easily locate and access the products and services offered in Susuk Village. Moreover, this initiative helps improve the digital literacy of MSME actors, particularly in understanding the importance of maintaining an online presence in a technology-driven economy. The availability of more professional business profiles on digital platforms also increases consumer trust and opens broader marketing opportunities. Overall, digital mapping through Go Maps proves to be an effective strategy for strengthening MSME competitiveness and supporting sustainable local economic development.